(untitled) (The Journal of Psychology and Sociology, 2012)
In article the work role in social development and life of the certain person is analyzed. The main sociological ap- proaches to work studying as fundamental activity of society are considered. Features of investigation of work and labor activity at different stages of society development and sociological science are shined. Authors note importance of study- ing of work as universal and national factor of development.